Music Composition Banyu Milir | Komposisi Musik Banyu Milir - Darmawan I Made Yudi; I Gde Made Indra Sadguna (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Subak is an organization owned by farming communities in Bali that specifically regulates the management or irrigation system/irrigation of rice fields traditionally. Banyu Milir composition uses instruments such as drums, reong, kajar, ceng-ceng ricik, jublag, jegog, gong, kemong, flute and there are two additional instruments, namely the kempur and cedugan drums. Through the creation of this work, the stylist wants to develop a pattern that has existed before, this development is in accordance with the musical elements of the stylist's interpretation, namely expressing something that is in the stylist's mind that will be poured into the gamelan that has been determined by the stylist. Banyu Milir's innovative musical work is elevated to a work as a reflection and a message to us that water is an important element that cannot be separated from living things. The process of composing Banyu Milir's innovative musical works has gone through five stages, namely the Inspiration Stage (Ngawirasa) The Exploration Stage (Ngawacak) The Conception Stage (Ngarancana) The Execution Stage (Ngawangun) The Production Stage (Ngebah), Banyu Milir's innovative musical work consists of three main parts, namely part one, part two and part three. This piece is supported by 17 musicians from Sanggar Mekar Seruni with a duration of approximately 12 minutes.